1994
DOI: 10.1007/bf00165815
|View full text |Cite
|
Sign up to set email alerts
|

Copper resistance in Anabaena variabilis: Effects of phosphate nutrition and polyphosphate bodies

Abstract: A copper-resistant Anabaena variabilis strain was obtained after repeated culturing in progressively higher concentrations of Cu(NO3)2. This strain maintained its resistance even after a year of repeated subculturing in copper-free medium. The resistant strain differed from the sensitive parent strain with respect to filament length, cell shape and size, and control of heterocyst formation. The resistant strain was also more resistant to cadmium, zinc, and nickel. Copper distribution studies conducted with ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…47,48 Investigations with a strain of Cu-sensitive and Cu-tolerant freshwater cyanobacterium, Anabaena variabilis, indicated that the tolerant strain contained more polyphosphate bodies than the sensitive strain and, even more polyphosphate bodies were observed after exposure to Cu. 47 However, X-ray microanalyses showed that Cu did not co-localise with these polyphosphate bodies (identified after staining with toluidine blue and microscopy), with only P and Ca detected. 47 Instead, Cu was detected in the cytoplasm (co-located with P, S, Ca, Mg, Si and S).…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Investigations with a strain of Cu-sensitive and Cu-tolerant freshwater cyanobacterium, Anabaena variabilis, indicated that the tolerant strain contained more polyphosphate bodies than the sensitive strain and, even more polyphosphate bodies were observed after exposure to Cu. 47 However, X-ray microanalyses showed that Cu did not co-localise with these polyphosphate bodies (identified after staining with toluidine blue and microscopy), with only P and Ca detected. 47 Instead, Cu was detected in the cytoplasm (co-located with P, S, Ca, Mg, Si and S).…”
Section: Discussionmentioning
confidence: 99%
“…Twiss and Nalewajko [46] observed that increasing the amount of cellular polyphosphate in UTEX 72 was very effective in reducing Cu toxicity to photosynthesis but was relatively insignificant in B4 and Cu-Tol. Polyphosphate bodies may have some effect on Cu resistance in Anabaena variabilis but are not completely responsible for this resistance [8].…”
Section: Discussionmentioning
confidence: 99%
“…Acidocalcisomal poly P stores are important for resistance to heavy metals in some eukaryotes and prokaryotes (Hashemi et al 1994;Alvarez & Jerez 2004;Andrade et al 2004;Remonsellez et al 2006;Nagasaka & Yoshimura 2008). Thus, phosphate and heavy metal storage may represent an ancestral characteristic that was important for their evolutionary development.…”
Section: Introductionmentioning
confidence: 99%